Ekologi Serdang (Livistona sp.) di Kecamatan Sekernan dan Kecamatan Mendahara Ulu: Serdang (Livistona sp.) Ecology in Sekernan Sub-Districd and Mendahara Ulu Sub-District - Nursanti, Nursanti; Adriadi, Ade Adriadi; Puji Astuti, Dwi (Universitas Jambi, 2023)
Livistona is one of the genera of palm plants with a wide distribution area, ecologically diverse and of horticultural, economic and ecological importance. The Livistona genus is an important ornamental plant species for landscapes, and generally tolerates it as an indoor (Siregar, 2005). The purpose of this study was to determine the ecology of Serdang (Livistona sp.) in Sekernan District and Mendahara Ulu District. This research was conducted in SeptemberOctober 2021 based on the purposive sampling method. The results obtained are Serdang ecology (Livistona sp.) Sekernan and Mendahara Ulu subdistricts found 16 serdang individuals, the composition of vegetation at the study site for tree stadia population was only slightly in secondary forest cover found 8 species of trees, while for oil palm plantations/rubber plantations there were 5 tree species, for the pole level most were found in oil palm plantations/rubber plantations with a total of 5 species while in secondary forest only 3 species, the sapling level was mostly found in oil palm plantations/rubber plantations because in rubber plantations the community allowed their gardens to be grown other than rubber, the seedling rate was mostly found in oil palm/rubber plantations with a total of 29 species with 129 individuals compared to secondary forests. Ecological factors around the herbaceous plants for humidity range from 250C–310C. The condition of the soil at the research site is sandy soil with a pH of 4.00 – 5.06. The slope of the medium-growing area is between 8% to 21%, which means that the herbaceous plant grows on the slope of the sloping to moderately steep area. Keywords: Livistona, Vegetation, Ecological Factors Abstrak Livistona adalah salah satu dari marga tumbuhan palma yang wilayah penyebarannya lebar, ekologinya beragam dan bernilai penting secara hortikultura, ekonomi dan ekologi. Livistona adalah jenis tumbuhan hias yang penting untuk landskap, dan umumnya toleransi sebagai tanaman dalam ruang (Siregar, 2005). Tujuan penelitian ini mengetahui ekologi serdang (Livistona sp.) di Kecamatan Sekernan dan Kecamatan Mendahara Ulu. Penelitian dilaksanakan pada bulan September-Oktober 2021 berdasarkan metode purposive sampling. Hasil penelitian ekologi serdang (Livistona sp.) Kecamatan Sekernan dan Kecamatan Mendahara Ulu ditemukan 16 individu serdang, Komposisi vegetasi dilokasi penelitian stadia pohon populasinya hanya sedikit pada tutupan hutan sekunder ditemukan 8 spesies pohon, sedangkan untuk kebun sawit/kebun karet terdapat 5 spesies pohon, tingkat tiang paling banyak ditemukan di tutupan kebun sawit/kebun karet dengan jumlah 5 spesies sedangkan di hutan sekunder hanya 3 spesies, tingkat pancang banyak di temukan pada tutupan kebun sawit/kebun karet karena pada kebun karet masyarakat membiarkan kebunnya ditumbuhan selain karet, tingkat semai banyak ditemukan di kebun sawit/kebun karet dengan jumlah 29 spesies dengan individu 129 dibandingkan hutan sekunder. Faktor ekologi di sekitar tumbuhan serdang kelembaban berkisar 250C–310C. Keadaan tanah di lokasi penelitian yaitu tanah berpasir dengan pH 4.00 – 5.06. Kemiringan tempat tumbuh serdang antara 8% hingga 21% bearti tumbuhan serdang tumbuh di kemiringan tempat landai hingga agam curam. Kata kunci: Livistona, Vegetasi, Faktor Ekologi